العلاقة بين الثقافة التنظيمية وقيادة الذات: دراسة تطبيقية على العاملين بقطاع البنوك التجارية في محافظة دمياط - عمارة، آثار إبراهيم حسن; حسانين، جاد الرب عبدالسميع Hassanein, Jadulrab Abdulsamia (جامعة بنها - كلية التجارة, 2019)
استهدفت هذه الدراسة بحث طبيعة العلاقة بين الثقافة التنظيمية وقيادة الذات العاملين بقطاع البنوك التجارية في محافظة دمياط، بالإضافة إلى التعرف على طبيعة تأثير أبعاد الثقافة التنظيمية على ابعاد قيادة الذات، وتم جمع البيانات من خلال قائمة استقصاء تم إعدادها واختبار صدقها وثباتها، وزعت على عينة بلغ حجمها 206 مفردة تم اختيارها عشوائيا والقيام بتحليلها اعتمادا على الأساليب الإحصائية المناسبة لطبيعة هذه البيانات حتى تتمكن الباحثة من التحقق من صحة الفروض. وقد توصلت الباحثة إلى عدة نتائج اهمها وجود علاقة ارتباط ذات دلالة إحصائية بين أبعاد الثقافة التنظيمية وكلا من الجوانب المادية والجوانب الحدسية لقيادة الذات، فضلا عن وجود تأثير معنوي للثقافة التنظيمية على كلا من الجوانب المادية والجوانب الحدسية لقيادة الذات.
“The relation between organizational culture and self-leadership: Applied to employee in Commercial Banks Sector at Damietta Governorate." This study aims to identify the nature of the relationship between organizational culture and self-leadership. AS well as, it aims to identify the nature of the impact of organizational culture on self-leadership applied to Commercial Banks Sector at Damietta Governorate. In order to collect primary data, a questionnaire was designed and data had been collected from a random sample which size was 206, and statistical method analysis based on appropriate to the nature of this data in order to validating hypotheses of the study. Results of the study showed that all dimensions of organizational culture were positively related with all dimensions of self-leadership. Also results showed that organizational culture had a significant effect on the symbolic and subjective components of self-leadership & the material and objective aspects of self-leadership.
Keywords: إدارة الموارد البشرية -- الثقافة التنظيمية -- قيادة الذات -- البنوك التجارية